Household Consumer’s Preferences And Demand For Granulated Sugar In Bandar Lampung City - Selly Muchtar Djalil; Fembriarti Erry Prasmatiwi; Teguh Endaryanto (Politeknik Negeri Lampung, 2021)
This study aims to The purpose of this study was to analyze the preferences, demands and determinants of household consumer sugar demand in Bandar Lampung City. The research data were collected in Kemiling, Way Halim, Tanjung Karang Barat and Tanjung Karang Timur subdistricts, Bandar Lampung City. The method used is a survey method with multistage random sampling technique. Research respondents were housewives totaling 100 households. Data analysis used conjoint analysis, descriptive statistical methods and multiple linear regression. Data collection was carried out in January-March 2021. The result is that the sugar that consumers prefer is packaged sugar with a smooth texture and white color, measuring one kilogram with a price range of Rp. 11.500 – Rp. 13,000. The product attributes that are considered the most important to the least important in order are the attributes of type, texture, color, size, and price. The pattern of household consumer sugar demand based on the brand that is widely used is Gulaku sugar with an average sugar purchase of 0.57 kilograms per capita per month. The determinants of demand for granulated sugar are the price of sugar and the number of family members.